Integrative multi-omics analysis reveals the contribution of neoVTX genes to venom diversity of Synanceia verrucosa - Zhiwei Zhang; Qian Li; Hao Li; Shichao Wei; Wen Yu; Zhaojie Peng; Fuwen Wei; Wenliang Zhou (BMC Genomics)
Abstract Background Animal venom systems are considered as valuable model for investigating the molecular mechanisms underlying phenotypic evolution. Stonefish are the most venomous and dangerous fish because of severe human envenomation and occasionally fatalities, whereas the genomic background of their venom has not been fully explored compared with that in other venomous animals. Results In this study, we followed modern venomic pipelines to decode the Synanceia verrucosa venom components. A catalog of 478 toxin genes was annotated based on our assembled chromosome-level genome. Integrative analysis of the high-quality genome, the transcriptome of the venom gland, and the proteome of crude venom revealed mechanisms underlying the venom complexity in S. verrucosa. Six tandem-duplicated neoVTX subunit genes were identified as the major source for the neoVTX protein production. Further isoform sequencing revealed massive alternative splicing events with a total of 411 isoforms demonstrated by the six genes, which further contributed to the venom diversity. We then characterized 12 dominantly expressed toxin genes in the venom gland, and 11 of which were evidenced to produce the venom protein components, with the neoVTX proteins as the most abundant. Other major venom proteins included a presumed CRVP, Kuntiz-type serine protease inhibitor, calglandulin protein, and hyaluronidase. Besides, a few of highly abundant non-toxin proteins were also characterized and they were hypothesized to function in housekeeping or hemostasis maintaining roles in the venom gland. Notably, gastrotropin like non-toxin proteins were the second highest abundant proteins in the venom, which have not been reported in other venomous animals and contribute to the unique venom properties of S. verrucosa. Conclusions The results identified the major venom composition of S. verrucosa, and highlighted the contribution of neoVTX genes to the diversity of venom composition through tandem-duplication and alternative splicing. The diverse neoVTX proteins in the venom as lethal particles are important for understanding the adaptive evolution of S. verrucosa. Further functional studies are encouraged to exploit the venom components of S. verrucosa for pharmaceutical innovation.